2012
DOI: 10.1111/j.1440-1754.2011.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of steroids in children with multiple recurrences of intussusception

Abstract: We describe the case of a boy who had 9 recurrences of intussusception, for which no pathological lesion at the leadpoint was identified. A contrast follow-through study revealed a follicular/nodular mucosal pattern, particularly prominent in the terminal ileum and caecum. Patients with multiple recurrences usually have an identifiable lesion at the leadpoint, but sometimes recurrences may be due to lymphoid hyperplasia, as presumed in our case. No further recurrences occurred after a two month tapering course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Yet, it is surprising that has been no mention of this therapeutic modality in the current literature. 10,[12][13][14] In our present study, early recurrence of intussusception was noted to be much less in the Dexamethasone group, in comparison to the non-Dexamethasone group, which is in concordance to the study by Essa et al who evaluated the role of Dexamethasone in decreasing early recurrent intussusception and reported a higher incidence of early recurrent intussusception in the control group (14%) compared to the treated group (2.5%). 8 In a study by Long et al who compared contrast media, imaging modalities, pharmacologic adjuvants, protocols for delayed repeated enema, surgical approaches and other curative techniques for intussusception management, it has been reported that dexamethasone intramuscularly as an adjuvant therapy may reduce intussusception recurrence after air or liquid enema and is preferred as a medical measure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yet, it is surprising that has been no mention of this therapeutic modality in the current literature. 10,[12][13][14] In our present study, early recurrence of intussusception was noted to be much less in the Dexamethasone group, in comparison to the non-Dexamethasone group, which is in concordance to the study by Essa et al who evaluated the role of Dexamethasone in decreasing early recurrent intussusception and reported a higher incidence of early recurrent intussusception in the control group (14%) compared to the treated group (2.5%). 8 In a study by Long et al who compared contrast media, imaging modalities, pharmacologic adjuvants, protocols for delayed repeated enema, surgical approaches and other curative techniques for intussusception management, it has been reported that dexamethasone intramuscularly as an adjuvant therapy may reduce intussusception recurrence after air or liquid enema and is preferred as a medical measure.…”
Section: Discussionsupporting
confidence: 92%
“…1,8 -12 The first successful surgical reduction in a paediatric patient was performed in 1871 by Jonathan Hutchinson. 12,13 By 1905, Harald Hirschsprung had accumulated 107 cases of hydrostatic enema reduction, nevertheless the treatment of intussusception in children was predominantly surgical until the mid-twentieth century. 2,8,9 The classical triad of intussusception are abdominal pain, palpable abdominal mass, and red currant jelly stools is quite rare and present in less than 15% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…ILH, a result of enhanced immune response to foreign antigens such as virus, bacteria and food components in young children [ 11 ], is a rare cause for IR [ 6 ]. A few case reports have shown that corticosteroids are effective for the treatment of ILH-induced IR in children [ 12 14 ]. In contrast, we observed that IR was not responsive to dexamethasone.…”
Section: Discussionmentioning
confidence: 99%